La lecture d’album au cycle 3 : regard réflexif sur quelques choix d’une équipe de recherche pluricatégorielle et pluridisciplinaire - Anne Leclaire-Halté (Recherches en Éducation)
This article gives a reflexive point of view on a research habit in the teaching of French. Its purpose is to shed light on the choices made by a multi-categorical and multidisciplinary team regarding the creation of a teaching sequence designed to train teachers. This sequence was created after some observations were made during a descriptive research phase on regular habits concerning the reading of picture books from third grade to fifth grade. The sequence is based on choices that take into account the richness of knowledge and experience of the different research team members. As reading the picture book used for the sequence raises the question of the processing of values at school, this point will also be discussed.